2012
DOI: 10.1002/syn.21543
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and parallel monitoring of neuroinflammation and neurodegeneration in a 6‐hydroxydopamine rat model of Parkinson's disease

Abstract: As neuroinflammatory processes are involved in the pathogenesis of Parkinson's disease (PD), we achieved the longitudinal evaluation of them in parallel with the modifications of dopaminergic function at several time-points after 6-hydroxydopamine (6-OHDA) lesion in the rat mimicking an early stage of PD. After unilateral intrastriatal 6-OHDA administration, we quantified the temporal evolution of the 18 kDa translocator protein (TSPO), TH-immunoreactivity and dopamine transporters in the striatum and substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
5
41
0
Order By: Relevance
“…In hemiparkinsonian rats, the bulk of DA neuron loss occurs within the first 7 days [3337]. Our early intervention began 3 days after lesion, suggesting that XPro®1595 can attenuate an ongoing degenerative process in which inflammation is a necessary component.…”
Section: Discussionmentioning
confidence: 99%
“…In hemiparkinsonian rats, the bulk of DA neuron loss occurs within the first 7 days [3337]. Our early intervention began 3 days after lesion, suggesting that XPro®1595 can attenuate an ongoing degenerative process in which inflammation is a necessary component.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when the neurotoxin was infused directly into axons, microgliosis preceded striatal terminal degeneration and occurred together with nigral degeneration (Walsh et al, 2011). Evaluation of 3 H-PK11195 autoradiography from rats administered unilateral intrastriatal 6-OHDA showed early strong microgliosis in the striatum starting 3 days after toxin delivery, but delayed and progressive increases in radiotracer density in the SN, synchronous with the timeline of degeneration (Maia et al, 2012). Overall, studies performed in toxin-based models support early and enduring microglia activation in the course of DA neuronal loss.…”
Section: Microgliosis In Models Of Pd-like Degenerationmentioning
confidence: 99%
“…Likewise, it has been shown that pro-inflammatory cytokines and chemokines are abundant in several brain regions and cerebrospinal fluid of PD patients (Boka et al, 1994;Mogi et al, 1994aMogi et al, ,b, 1995Mogi et al, , 2007Shimoji et al, 2009). In experimental PD models, glial activation occurs transiently in the injection site of neurotoxin used to cause dopaminergic neuronal death (Banati et al, 1998), accompanying the neuronal degeneration (Henry et al, 2009;Maia et al, 2012). However, the pattern of neuroinflammatoryglial activation seen in our study was clearly caused by L-DOPA treatment, and it was not due to the 6-OHDA lesion per se, as discussed above.…”
Section: Glial Mechanisms In L-dopa Induced Dyskinesiamentioning
confidence: 99%